(3OjhGf aJjGf GdTGZhQjs - (3TgGH GdOjf CHheMeO aJjGf Hf Ydj Hf aJjGf Hf KeGd GdCSOj GdTGZhQj,J (B615 (3g` s ((3Ydj Hf CHj UYH Hf Ydj Hf GdMSjf GdMdHj s)
(3ChdgG (B:s
(3GdMeO ddg GdbOjQ adG jYLRg eJhge gPG eG hLOJg afbdJg ef eShOGJ hLOJgG HNW hGdOj Edi eMeO aJjGf ef TYQ dfaSg QMeg Gddg, hbO LeYJg Ydi MQha GdeYLe s
(3BNQgG (B:s
(3CfJ YfOj MRjeg GdTGgO GdUGOb EPG cGf TGgOkG ddfHj Je LejY GdeNJGQ ef TYQ GdTjN aJjGf Hf Ydj GdfMhj s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B336 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B54s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B173 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs